Pediatric disorders current topics and interventions for educators - McCabe, Paul C.; Shaw, Steven R.; Sage eBooks; National Association of School Psychologists (Thousand Oaks, Calif. : Corwin, 2010)
This concise and well-researched investigation into pediatric health issues provides credibility and verifiability of data and establishes a foundation of confidence for any educator who must make policy, differentiate instruction, provide educational accommodations, offer special education services, and much more.
"A joint publication with the National Association of School Psychologists."
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School health services -- Handbooks, manuals, etc; Children -- Diseases -- Treatment -- Handbooks, manuals, etc; Pediatrics -- Handbooks, manuals, etc; Electronic books